Official Development Assistance Effect on Infant Mortality and Human Development Index: Asia Evidence - Herdika, Rizky; Handoyo, Rossanto Dwi; Hudang, Adrianus Kabubu; Haryanto, Tri (Journal of Developing Economies, 2022)
Official Development Assistance (ODA) is a program formed by the Development Assistance Committee (DAC) which aims to improve country development and eradicate poverty in developing countries. Many Asian countries are ODA recipients. The purpose of this study is  to determine the effect of ODA on infant mortality and the Human Development Index. The method used is panel data regression. Estimation results show that ODA has a significant effect on HDI, but not significantly on infant mortality.JEL Classification Codes : F10; F35; I15